The development of bengkung in the context of Malay culture / Norizan Sajar - Sajar, Norizan (2023)
Bengkung and ikat pinggang are Malay practices in the belly binding method. The problem with the research is that most researchers only provided a broad overview of bengkung and did not go into specific depth about the design and its details. There is a gap in the categorization of bengkung as well. Another problem being addressed regarding bengkung is its neglection as a Malay tradition because it lacks written documentation. The aim of this research is to document the development of bengkung design in the context of Malay culture. The research objectives are to identify the design of bengkung, categorize the type of bengkung used, and determine the uniqueness of bengkung practice in the context of Malay culture. This research emphasizes on the bengkung design and style in the Malay culture. The methodology of this research is a qualitative research, which is a descriptive approach and observation of bengkung made based on the theory of style by Meyer Schapiro. The primary data of this research study are photo images and samples of the bengkung design. In this research, an interview was conducted with an expert in the field of midwifery, as well as with a specialist in Malay clothing, to identify and describe the history and design of the bengkung, as well as its types, patterns, materials, design details, and functions of the bengkung using the narrative approach. Data analysis involved three components of the theory of style, which are form, element, and expression. The finding of this research is based on the bengkung design and style of bengkung from the year 1950 until the year 2000 in which the design is produced or used. The research discovered that the many varieties of bengkung may be divided into three categories: bengkung for health, bengkung for beauty, and bengkung and ikat pinggang as complementary accessories in Malay clothing. The uniqueness of practicing the bengkung is different based on the categorization and function of bengkung. Our beliefs and positivity toward wearing bengkung help in making the bengkung more valuable and effective. Furthermore, the research provides sufficient information about the design and function of the bengkung as part of the culture, and as a reference and guideline for scholars, future researchers, educators, health services, midwives, and practitioners. The knowledge of bengkung practice will motivate future generations to be more appreciative of cultural heritage and hence, encourage the preservation of culture and practice.